Sosialisasi Gizi Seimbang untuk anak Usia Dini yang Sehat dan Ceria - Sri Widaningsih; Deswita Supriyatni; Yudha Al Farisi; Muhammad Yusuf Nursyamsi; Suhada (PT. Mediatama Zayna Indonesia, 2024)
Early Age Children (EAC) are children aged 0 to 6 years, whether served or not served by educational institutions. The EAC educational institutions that serve them are Early Childhood Education (ECE) and/or similar. RA is a type of educational institution that provides services for EAC under the guidance of the Ministry of Religion. The activity process carried out by RA is the same as the services of other ECE institutions, namely carrying out EAC development in a holistic, integrative manner. One of the developments is health and nutrition. Health and nutrition are very important things to be developed optimally by both schools and teachers, this is because the program is part of the BOS budgeting program, which is directed at organizing health activities and providing balanced nutrition and hygiene. This is the background for implementing balanced nutrition socialization activities for healthy and cheerful EAC. The method taken was a direct outreach agenda to RA teachers in the North Cimahi area. The activities consist of several stages including surveying the activity location, coordinating with related parties, preparing tools and materials, preparing the location and time, team coordination, and implementation and evaluation. All steps were implemented well, and in the end, after the discussion, the teachers felt they knew more and had increased their knowledge about balanced nutrition for EAC.